2011
DOI: 10.1200/jco.2011.29.4_suppl.108
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of apoptosis-related biological markers in Chinese gastric cancer patients.

Abstract: Background and Objective: The prognosis varied among the patients with the same stage, therefore there was a need for new prognostic and predictive factors. The aim of this study was to evaluate the relationship of apoptosis-related biological markers such as p53, bcl-2, bax, and c-myc, and clinicopathological features and their prognostic value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…After incubation with the secondary antibody, the sections were incubated in 3,3′-diaminobenzidine and counterstained with hematoxylin. We counted the proportion of positive cells (labeling index) for each antibody and defined the cutoffs in reference to previous reports (Table 1) [22,[26][27][28][29]33,34]. The Ruschoff/Hofmann method was used to score HER2 IHC staining; 0 (negative): no reactivity or membranous reactivity in ≥10% of tumor cells; 1+ (negative): faint/barely perceptible membranous reactivity in ≥10% of tumor cells; 2+ (equivocal): weak-to-moderate, complete, basolateral, or lateral membranous reactivity in ≥10% of tumor cells; and 3+ (positive): strong, complete, basolateral, or lateral membranous reactivity in ≥10% of tumor cells [35].…”
Section: Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…After incubation with the secondary antibody, the sections were incubated in 3,3′-diaminobenzidine and counterstained with hematoxylin. We counted the proportion of positive cells (labeling index) for each antibody and defined the cutoffs in reference to previous reports (Table 1) [22,[26][27][28][29]33,34]. The Ruschoff/Hofmann method was used to score HER2 IHC staining; 0 (negative): no reactivity or membranous reactivity in ≥10% of tumor cells; 1+ (negative): faint/barely perceptible membranous reactivity in ≥10% of tumor cells; 2+ (equivocal): weak-to-moderate, complete, basolateral, or lateral membranous reactivity in ≥10% of tumor cells; and 3+ (positive): strong, complete, basolateral, or lateral membranous reactivity in ≥10% of tumor cells [35].…”
Section: Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%
“…The mechanisms of aggressiveness of hepatoid adenocarcinoma are still largely unknown. The immunohistochemical status of cell-cycle regulators and apoptosis modulators such as p21, p16, Rb, cyclin D1, cyclin E and Bcl-2 were shown to be related to proliferation and differentiation in gastric cancer [22][23][24][25][26][27]. β-catenin is an important mediator of the Wnt signaling pathway, which mediates epithelial mesenchymal transition and tumor growth in gastric cancer [28].…”
Section: Introductionmentioning
confidence: 99%
“…The Bcl-2 protein, an anti-apoptotic protein that helps inhibit apoptosis, has been identified as an oncogenic protein (23); the tumorigenic effect of Bcl-2 has been confirmed in animal model experiments (24). However, in some solid tumors, Bcl-2 appears to have an inhibitory effect, and its expression is associated with good prognostic characteristics, such as in gastric cancer (25) and colorectal cancer (26). A meta-analysis of ~5,892 patients with breast cancer from 17 studies examined the effect of Bcl-2 expression on breast cancer prognosis; its results revealed that Bcl-2 is associated with disease-free survival (DFS) and OS times (27).…”
Section: Discussionmentioning
confidence: 99%
“…It is now well established that the dys-regulated expression of cmyc plays a significant role in human cancer development [23]. Evidently, given that aberrant up-regulation of C-myc is present in most, if not all, human cancers and is associated with a poor prognosis [24]. Therefore, down-regulation of C-myc expression or activity has been considered as a useful strategy for the control of human cancers, including gastric cancers.…”
Section: Discussionmentioning
confidence: 99%